Optimizing bay dimension in mixed pyramid stacking storage systems - Jang, Dong-Won; Kim, Kap Hwan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
Pyramid stacking is a type of block stacking method for cylindrical unit loads such as drums, coils, paper rolls, and so on. This study addresses how to determine the dimension (height and width) of a bay. It is assumed that multiple types of unit loads, which have different retrieval rates and duration of stays from each other, are stored in the same bay. A cost model is proposed to determine the optimal dimension of a bay. A numerical example is provided to illustrate the procedure for the optimization in this paper.